Legum Studia Penyelesaian Sengketa Harta Bersama - Syarifuddin, Jaka Syahrial; Karim, Kairuddin; Suardi, Suardi (Jurnal Litigasi Amsir, 2021)
Determining the status of property ownership during the marriage is important to obtain clarity on the position of the property in the event of the death of one of the husbands or wives, which is the inheritance that will be inherited by their respective heirs. This study aims to find out and understand the legal review of joint property disputes that occurred after the divorce based on Decision Study Number: 285/Pdt.G/2019/PA.Pare. This research uses empirical normative research with a statutory approach and a case study approach. The results of the study show that the process of dividing joint assets due to divorce based on law and fiqh has prioritized the principle of justice. In the process, there is a clear picture of the case that occurred so that the judge can determine and decide on the distribution of joint property following the Marriage Law Number 1 of 1974 and the Compilation of Islamic Law.